Computational Analysis of Fluid Structure Interaction in Artificial Heart Valves - Yeh, Han Hung; Grecov, Dana; Karri, Satya (CMBES Proceedings, 2013)
This study presents numerical simulations of a minimum constrained mechanical valve using fully coupled fluid structure interaction (FSI) of COMSOL Multiphysics, a finite element based software. The present model applies a physiological pulsatile pressure gradient across the valve with an approximate symmetric aortic root. The complex hinge from the exact model is simplified with a pin joint with weak constrains to control the fully opened and closed position of the valve. The Arbitrary Lagrangian-Eulerian method is applied in order to accommodate the large mesh displacement due to leaflet motion. Constant material properties are applied to both fluid and structure with the assumption that the flow is Newtonian and turbulent. Overall, the valve leaflet positions and flow patterns are verified against results from literature. Simulations on mechanical valve malfunction identify the generation of vortices, which may suggest regions of high and low velocity for further evaluation.